Modified fractal rectangular curve dielectric resonator antenna terminated in a bio-medium - Gangwar R.K.; Singh S.P.; Kumar D. (My University, 2025)
A modified fractal rectangular curve Dielectric Resonator Antenna (DRA) with a hole/holes has been proposed for 2.4 GHz WLAN band and its input and radiation characteristics compared with conventional FRC-1 DRA of same size through simulation studies using CST Microwave Studio software. The effects of the size, position and shape of hole/holes introduced in the fractal geometry on the characteristics of the antenna have also been studied. Furthermore, simulation results for absorbed power distribution in a homogeneous bio-medium (muscle layer) owing to the proposed fractal antenna with five holes of square cross-section for different antenna-to-bio-media separations are presented in terms of Specific Absorption Rate (SAR) distribution in the medium at the resonant frequency of the antenna. Copyright © 2014 Inderscience Enterprises Ltd.